2018
DOI: 10.7752/jpes.2018.01026
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objective: To compare the effects of active video game-based (AVG) physical activity program with aerobic exercise on cognitive performance among healthy older adults. Methods: Individuals of both sexes, aged 55 years or older, were randomly assigned to either AVG group and aerobic exercise group (active control group). For AVG program, we used games that simulated sports activities (Xbox 360 Kinect tm). The aerobic exercise program (moderate intensity) was conducted on treadmills and cycle ergometers. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…It has recently been reported that a multi-component physical exercise program did not improve cognitive function in participants with type 2 diabetes, perhaps because of the characteristics of the exercises program and the methodology design [63]. However, our results agree with several recent studies that reported improvements in cognitive deterioration in older women who carried out an aerobic exercise programme [64][65][66][67]. On the other hand, the CG showed a worse cognitive state after the 24-week study period, with a significant decrease in MMSE score (p < 0.001).…”
Section: Glycosylated Haemoglobinsupporting
confidence: 86%
“…It has recently been reported that a multi-component physical exercise program did not improve cognitive function in participants with type 2 diabetes, perhaps because of the characteristics of the exercises program and the methodology design [63]. However, our results agree with several recent studies that reported improvements in cognitive deterioration in older women who carried out an aerobic exercise programme [64][65][66][67]. On the other hand, the CG showed a worse cognitive state after the 24-week study period, with a significant decrease in MMSE score (p < 0.001).…”
Section: Glycosylated Haemoglobinsupporting
confidence: 86%
“…Given that exergames encourage the user to engage in physical activity, it is unsurprising that research in this area often focuses on their impact on physical health outcomes, such as levels of balance and cardiovascular health. For example, studies show that engaging in an exergame regimen significantly improves balance, flexibility, braking force, lower-limb muscle strength, maximal oxygen levels, and heart rate (Maillot, Perrot, Hartley, & Do, 2014; Nitz, Kuys, Isles, & Fu, 2010; Roopchand-Martin, Nelson, Gordon, & Sing, 2015), although a combination of exergames and traditional exercise has been shown to have the highest benefits on physical well-being (Guimarães, Barbosa, & Meneghini, 2018; Toulotte, Toursel, & Olivier, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the used exergames involved complex, upper-limb, lower-limb and whole-body movements. In a few studies, games were categorized as a function of the physical/motor capacities they prominently required (i.e., endurance, strength, motor coordination, motor ability, balance control…) (e.g., Maillot et al, 2012 ; Ordnung et al, 2017 ; Bacha et al, 2018 ; Guimarães et al, 2018 ; Gouveia et al, 2021 ; Moreira et al, 2021 ; for an illustration, Peng et al, 2020 ). On the other hand, their cognitive contents were scarcely precisely described (for an exception, Bacha et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Different commercial products were used to implement MDT. The Xbox Kinect console (+ Kinect sensors allowing to control an avatar) was the most frequently used ( Kayama et al, 2014 ; Ordnung et al, 2017 ; Bacha et al, 2018 ; Guimarães et al, 2018 ; Htut et al, 2018 ; Moreira et al, 2021 ), together with the Nintendo Wii package ( Maillot et al, 2012 ) and Dance Dance Revolution ( Chuang et al, 2015 ). Lab-customized exergames were also used in two studies ( Peng et al, 2020 ; Gouveia et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%